"A good translator can be androgynous": an interview with Niaz Zaman. Issue 1 (2nd January 2022) - Islam, Mohammad Shafiqul
ABSTRACT: Niaz Zaman, a renowned academic, translator, editor, essayist, and writer, has been translating Bengali literature into English for a long time. Her translation works, which are widely read, are critically acclaimed as well. She has translated numerous books and anthologies, and edited a great number of short story collections. Well known as a translator of Kazi Nazrul Islam, the national poet of Bangladesh, she has also carried across classical, modern, and contemporary voices of Bengali literature. An inspiring figure of literary translation, she promotes emerging translators from Bangladesh, showcasing their work in various anthologies. In this interview, Zaman addresses various issues of translation in general and literary translation in particular, giving an account of her wide range of translation works. The interview, conducted online during May, June, and July 2021, also focuses on her individual strategies and techniques of translation, her inspirations and a long journey in the realm of literary translation, and her general observations and comments on translation.